Managing water through livestock in the Nile basin - Peden, Donald G.; Johnson, Nancy L. (CGIAR Challenge Program on Water and Food, 2009)
Livestock use and degrade much water in the Nile River Basin. New research suggests that integrated development and management of water and livestock resources will conserve water and increase the profitability and environmental sustainability of investments by governments, development agencies, and farmers. Practical opportunities exist to enhance food security, reduce poverty, and foster benefit sharing. Institutions responsible for water resources may benefit from partnering with the livestock sector when developing water resources.